Clinical study on treatment of non-acute knee osteoarthritis (KOA) using electro-acupuncture at top ten highly-researched acupoints - Yu, ShiChao (2024)
Osteoarthritis (OA) is a common chronic, degenerative joint disease, involves multiple anatomical and physiological changes of joint tissues and bone regeneration characterised by cartilage degradation and subchondral bone sclerosis. This results in symptoms of OA such as pain, stiffness, swelling, deformation and limited joint movement, and is the main cause of disability. The most common OA is Knee Osteoarthritis (KOA) which is a degenerative joint condition that primarily affects the knee joints. It is the most common form of arthritis and occurs when the protective cartilage that cushions the ends of the bones in the knee joint gradually wears away, and prolongs fiction of the bear joint structure causing inflammation which leads to pain, stiffness, swelling, deformation and limited mobility. Knee joints are essential for weight-bearing, locomotion and various physical activities. The dysfunction of knee-joints due to KOA greatly impacts the normal life of patients and in serious and extreme cases, poses a danger to lives. This problem needs to be addressed as there is an increased occurrence rate of KOA in both men and women, and the onset age is getting younger. Modern medical treatment for KOA such as non-pharmacological treatment, pharmacological treatment and surgical treatment, have their advantages and shortcomings. Non-pharmacological treatments require high discipline by the patients and usually take longer time to remedy and recover; pharmacological treatments such as the use of non-steroidal anti-inflammatory drugs (NSAIDs), can temporarily relieve the symptoms but require long-term use and lack supporting evidence of long-term efficacy; and surgical treatment has certain therapeutic effects, but it is still an invasive therapy which often brings great physical, psychological and economic burdens to patients. In traditional Chinese medicine (TCM), there are various methods of treating KOA such as Chinese herbal, massage, cupping and acupuncture which are simple, easy to implement, and easy to be accepted by patients. Acupuncture is a commonly used treatment method for KOA and has the advantages of simplicity, no toxicity side effects, and is easily accepted by patients. One of the acupuncture methods is Electroacupuncture (EA) which combines traditional acupuncture and modern electronic medicine, has definite efficacy and high safety, and has been widely used in KOA clinical therapy. In this research, the application of EA in KOA therapy has been studied and compared to other treatment methods to understand and determine its relevance and efficacy in improving the treatment, patient experience and worthiness of promotion in Malaysia and even, globally. The research study consisted of 3 parts - the questionnaire research, the literature research and the clinical research. In the questionnaire research, the application of TCM therapy methods in the treatment of KOA in Malaysian TCM clinics and hospitals was studied, analysed and compared with the situation in China. A questionnaire was designed surveying the age range of the patients and the TCM therapy methods for KOA, and was distributed to physicians in TCM clinics and hospitals in Malaysia and China. A total of 489 and 873 valid questionnaires were re-collected in Malaysia and China respectively. Based on the survey results, it was found that the onset age of KOA patients in Malaysia and China is concentrated between 50 to 59 years old which is in line with the characteristics of KOA where the high incidence rate is mainly in middle-aged and elderly people. The TCM methods commonly used in Malaysia vary such as Manual Acupuncture (MA) (81.60%), Massage (78.53%), Cupping (76.28%), Moxibustion (64.21%), Bloodletting (54.60%) and EA (48.26%). Contrarily in China, besides MA (93.13%), EA (84.19%) and Chinese Herbs (internal or external use) (80.53%) are frequently used for KOA treatment. The EA is widely used in China because of its precise curative effect and high safety, and has been incorporated into clinical pathways, second only to MA. The usage rate of EA in Malaysia is very low compared to in China and this trend could be due to the TCM physicians mainly focusing on non-invasive treatment methods such as Hot Compress Therapy, Scraping Therapy and Rehabilitation Treatment, which do not require deep knowledge and skills; and unified and standardised process when treating KOA and often rely on their familiarity with certain methods. Moreover, when evaluating clinical efficacy, it is mainly based on the patient's subjective self-perception and the physician's experience, lacking objective, standardized, and realistic evaluation criteria and systems. In the literature research study, the TCM theory of acupuncture for KOA was reviewed and analysed. The criteria of acupoint selection and features of acupoint use for acupuncture in the KOA’s clinical treatment were studied and examined in great detail based on literature search, data extraction and data analysis. The top ten high-frequency acupoints for acupuncture treatment of KOA were screened, identified and summarised; and provided a new and basic acupoint prescription for KOA, and to determine its suitability as a guide for clinical practice. The literature on randomized controlled trial (RCT) studies of acupuncture in the treatment of KOA over a defined period in the relevant databases of China National Knowledge Infrastructure (CNKI), Weipu Journal Full-text Database (VIP), Wanfang Data Knowledge Service Platform (Wanfang), China Biology Medicine disc (CBMdisc), PubMed and Embase were retrieved through computer and manual retrieval. After the data extraction was completed, the total number of occurrences of the acupoints used was counted and the number and rate of occurrences were used as indicators to analyse the frequency of use, channel tropism (the belongings to meridians), distance, locations of distribution, and the characteristics of acupoints (specific acupoint attributes). Statistical (descriptive) analysis of the relevant acupoints in the literature was conducted to explore the rules of acupoint selection and features of acupoint use in the treatment of KOA. The top ten highly-researched acupoints were specifically analysed. Based on the 2,264 papers studied, 139 frequently used acupoints in the KOA treatment with acupuncture were screened out from the 12 main meridians such as Ren meridians, Du meridians, and extraordinary points (acupoints beyond meridians). The top 10 high-frequency acupoints by descending order are ST35 (Dubi), EX-LE4 (Neixieyan), GB34 (Yanglingquan), SP10 (Xuehai), ST36 (Zusanli), ST34 (Liangqiu), SP9 (Yinlingquan), EX-LE2 (Heding), SP6 (Sanyinjiao) and GB33 (Xiyangguan). The total frequency of use of 21 selected acupoints from the proximal part (at close range) of the lower limbs, especially at or around the knee joint, is 14,137 times with the rate of occurrence being 82.97%. The literature research study also revealed that the total usage frequency of the two meridians Stomach Meridian of Foot Yangming and the Spleen Meridian of Foot Taiyin.ST & SP is 9,053 times (about 53.13%) and ranked in the top two. The number of specific acupoints accounted for 55.40% of the commonly used acupoints in acupuncture treatment of KOA, and the Five-shu acupoints and the He acupoints were the most used. From this study, it was concluded that the acupoints selected for acupuncture treatment of KOA are mainly concentrated on the Spleen and Stomach Meridians, and lower limbs. Acupoints from the proximal part, along the meridian, and specific acupoints are mainly selected, and supplemented by the acupoints from the far part. Among the specific acupoints, Five-shu acupoints and He acupoints are used the most. The above-mentioned top 10 high-frequency acupoints can be used as a new basic acupoint prescription for acupuncture treatment of KOA as this new acupoint prescription can tonify the body's healthy energy while dispelling pathogenic factors, with the characteristics of combining differentiation of disease and syndrome. The combination of the selected 10 acupoints can have effects such as enhancing blood circulation, removing blood stasis, strengthening the spleen, eliminating dampness, dispelling wind and dispersing cold, promoting the circulation of Qi and stopping pain, nourishing Qi and Blood, strengthening tendons and bones and be prescribed with taking into account both the proximal and distal acupoints. The results of the subsequent clinical research based on this acupuncture prescription have also confirmed its effectiveness, and the new prescription can be used as a guide for clinical practice. Upon identification of the top 10 highly-researched acupoints, the study proceeded with the clinical research study where RCT was used to validate the clinical effectiveness and to determine the scientific basis for the clinical efficacy of the acupoint prescriptions in the treatment of KOA. It is also important to explore the possible internal mechanism by which EA can treat KOA and improve its clinical symptoms. According to the result of sample size estimation and the ratio of 1:1:1, 207 eligible patients with KOA were randomly allocated into the Treatment Group (EA with the top ten highly-researched acupoints), Control Group 1 (Manual acupuncture (MA) with the top ten highly-researched acupoints), and Control Group 2 [Sham acupuncture (SA): MA with sham acupoints (the points does not belong to the main meridians and pain points)]. Each of the three groups will be treated with acupuncture once a day for 30 minutes each time. 6 times for a course of treatment, 2 courses in total, and take one day off between the two courses. Quantitative Score of Knee Osteoarthritis Symptom Classification (SKSC), Western Ontario and McMaster University Osteoarthritis Index (WOMAC), Lysholm Knee Score Scale (LKSS) and Visual Analogue Scale（VAS）were compared between the three groups before and after treatment. Venous blood was drawn from patients before and after treatment, and the changes in serum IL-1β and TNF-α were detected by EnzymeLinked Immunosorbent Assay (ELISA). The data collected from the clinical research were analysed using SPSS 22.0 software. From the results of the clinical research study, it was found that the three groups of patients were comparable in age, course of the disease, gender, and other baseline data, and the difference was not statistically significant (P > 0.05). The clinical effectiveness of the three groups of patients was as follows: the Treatment Group was 89.9%, the Control Group 1 was 75.4%, and the Control Group 2 was 5.8%; and there were statistically significant differences in the clinical effectiveness of the three groups (χ 2 = 113.690, P < 0.05). There was no statistical difference (P > 0.05) among the three groups before treatment in SKSC, WOMAC, LKSS, VAS, IL-1β, and TNF-α content, and they were comparable; after treatment, the differences in the above indicators among the three groups were statistically significant (P < 0.05). The intra-group comparison of the above indicators of the three groups showed that the difference between the Treatment Group and the Control Group 1 before and after treatment was statistically significant, and all P values were < 0.05. It was also discovered that compared with before treatment, the scores of SKSC, WOMAC, VAS, IL-1β, and TNF-α in the Treatment Group and Control Group 1 after treatment were significantly decreased, and these scores in the Treatment Group were significantly lower than those in the Control Groups, and all P values were < 0.05; the LKSS score was higher than that before treatment, and the score in the Treatment Group was significantly higher than that in the Control Groups, and P < 0.05, indicating that the treatments of the Treatment Group and Control Group 1 were effective, and the Treatment Group was better than the Control Group 1. However, the above observation indicators of Control Group 2 did not change much, and with P > 0.05, there was no statistical difference, indicating that the effect of Control Group 2 before and after treatment was not obvious. Based on the results of the clinical research study, it was concluded that both EA and MA combined with the top ten highly-researched acupoints have therapeutic effects on KOA. The two treatment methods both effectively improve clinical symptoms and signs of patients while reducing serum levels of inflammatory cytokines, including IL-1β and TNF-α. The EA yields better clinical efficacy compared to MA as it not only improves clinical symptoms but also enhances patients' quality of life. The acupuncture treatment at the points does not belong to the main meridians, acupoints and pain points, is not effective in treating KOA, and Sham Acupuncture does not exhibit a significant placebo effect, resulting in poorer clinical outcomes. Based on analysis, one of the proposed mechanisms of action for EA in treating KOA is its ability to regulate serum levels of IL-1β and TNF-α, ultimately reducing pro-inflammatory cytokines. The results of the clinical research study have validated the clinical efficacy and scientific basis of the acupuncture prescription used in the study, as well as the significant clinical efficacy of combining it with EA. Based on the questionnaire, literature and clinical research studies, it is concluded that the combination of EA with the top ten highly-researched acupoints is a simple, convenient, and effective treatment method for KOA. It is x also a safer, more efficient and easily implemented acupuncture treatment method for KOA, making it worthy of promotion in KOA treatment in Malaysia and can be extended to countries outside China. Key words: Electro-acupuncture; Top ten highly-researched acupoints; Knee osteoarthritis; IL-1β, TNF-α; Clinical research; Mechanism research.